Asymmetric synthesis of CF2-functionalized aziridines by combined strong Brønsted acid catalysis - Tan, Xing-Fa; Zhang, Fa-Guang; Ma, Jun-An (Beilstein Journal of Organic Chemistry, 2020)
A diastereo- and enantioselective approach to access chiral CF2-functionalized aziridines from difluorodiazoethyl phenyl sulfone (PhSO2CF2CHN2) and in situ-formed aldimines is described. This multicomponent reaction is enabled by a combined strong Brønsted acid catalytic platform consisting of a chiral disulfonimide and 2-carboxyphenylboronic acid. The optical purity of the obtained CF2-substituted aziridines could be further improved by a practical dissolution–filtration procedure.
Keywords: aziridines; chiral disulfonimides; difluoromethyl compounds; fluorinated diazo reagents; strong Brønsted acids

(untitled) - Tanner, D. (Angew. Chem., Int. Ed. Engl., 1994)

(untitled) - Sweeney, J. B. (Chem. Soc. Rev., 2002)

(untitled) - Singh, G. S.; D'hooghe, M.; De Kimpe, N. (Chem. Rev., 2007)

(untitled) - Sweeney, J. (Eur. J. Org. Chem., 2009)

(untitled) - Stanković, S.; D'hooghe, M.; Catak, S.; Eum, H.; Waroquier, M.; Van Speybroeck, V.; De Kimpe, N.; Ha, H.-J. (Chem. Soc. Rev., 2012)

(untitled) - de los Santos, J. M.; Ochoa de Retana, A. M.; Martínez de Marigorta, E.; Vicario, J.; Palacios, F. (ChemCatChem, 2018)

(untitled) - Muller, K.; Faeh, C.; Diederich, F. (Science, 2007)

(untitled) - Ma, J.-A.; Cahard, D. (Chem. Rev., 2008)

(untitled) - Nie, J.; Guo, H.-C.; Cahard, D.; Ma, J.-A. (Chem. Rev., 2011)

(untitled) - Meanwell, N. A. (J. Med. Chem., 2018)

(untitled) - Rong, J.; Ni, C.; Hu, J. (Asian J. Org. Chem., 2017)

(untitled) - Meyer, F. (Chem. Commun., 2016)

(untitled) - Dolfen, J.; De Kimpe, N.; D’hooghe, M. (Synlett, 2016)

(untitled) - Katagiri, T.; Ihara, H.; Takahashi, M.; Kashino, S.; Furuhashi, K.; Uneyama, K. (Tetrahedron: Asymmetry, 1997)

(untitled) - Colantoni, D.; Fioravanti, S.; Pellacani, L.; Tardella, P. A. (Org. Lett., 2004)

(untitled) - Maeda, R.; Ooyama, K.; Anno, R.; Shiosaki, M.; Azema, T.; Hanamoto, T. (Org. Lett., 2010)

(untitled) - Künzi, S. A.; Morandi, B.; Carreira, E. M. (Org. Lett., 2012)

(untitled) - Yang, Y.; Huang, Y.; Qing, F.-L. (Tetrahedron Lett., 2013)

(untitled) - Dolfen, J.; Kenis, S.; Van Hecke, K.; De Kimpe, N.; D'hooghe, M. (Chem. – Eur. J., 2014)

(untitled) - Wang, F.; Zhu, N.; Chen, P.; Ye, J.; Liu, G. (Angew. Chem., Int. Ed., 2015)

(untitled) - Duan, Y.; Zhou, B.; Lin, J.-H.; Xiao, J.-C. (Chem. Commun., 2015)

(untitled) - Huang, Y.-J.; Qiao, B.; Zhang, F.-G.; Ma, J.-A. (Tetrahedron, 2018)

(untitled) - Mészáros, Á.; Székely, A.; Stirling, A.; Novák, Z. (Angew. Chem., Int. Ed., 2018)

(untitled) - Thi, H. D.; Thuy, G. L. N.; Catak, S.; Van Speybroeck, V.; Nguyen, T. V.; D’hooghe, M. (Synthesis, 2018)

(untitled) - Wu, K.; Zhou, C.-Y.; Che, C.-M. (Org. Lett., 2019)

(untitled) - Chai, Z.; Bouillon, J.-P.; Cahard, D. (Chem. Commun., 2012)

(untitled) - Mae, M.; Matsuura, M.; Amii, H.; Uneyama, K. (Tetrahedron Lett., 2002)

(untitled) - Palacios, F.; Ochoa de Retana, A. M.; Alonso, J. M. (J. Org. Chem., 2006)

(untitled) - Liu, J.; Hu, J. (Chem. – Eur. J., 2010)

(untitled) - Kurosato, F.; Ishikawa, T.; Yamada, Y.; Hanamoto, T. (Synlett, 2015)

(untitled) - Zhang, W.; Wang, X.; Zhu, B.; Zhu, D.; Han, J.; Wzorek, A.; Sato, A.; Soloshonok, V. A.; Zhou, J.; Pan, Y. (Adv. Synth. Catal., 2017)

(untitled) - Zeng, J.-L.; Chen, Z.; Zhang, F.-G.; Ma, J.-A. (Org. Lett., 2018)

(untitled) - Peng, X.; Xiao, M.-Y.; Zeng, J.-L.; Zhang, F.-G.; Ma, J.-A. (Org. Lett., 2019)

(untitled) - Zeng, J.-L.; Zhang, Y.; Zheng, M.-M.; Zhang, Z.-Q.; Xue, X.-S.; Zhang, F.-G.; Ma, J.-A. (Org. Lett., 2019)

(untitled) - Zhang, Z.-Q.; Zheng, M.-M.; Xue, X.-S.; Marek, I.; Zhang, F.-G.; Ma, J.-A. (Angew. Chem., Int. Ed., 2019)

(untitled) - Zhang, Y.; Wang, J. (Chem. Commun., 2009)

(untitled) - Zhang, Y.; Lu, Z.; Wulff, W. D. (Synlett, 2009)

(untitled) - Pellissier, H. (Adv. Synth. Catal., 2014)

(untitled) - Liu, Y. (Curr. Org. Chem., 2016)

(untitled) - Yamamoto, H.; Futatsugi, K. (Angew. Chem., Int. Ed., 2005)

(untitled) - Dimitrijević, E.; Taylor, M. S. (ACS Catal., 2013)

(untitled) - Hashimoto, T.; Gálvez, A. O.; Maruoka, K. (J. Am. Chem. Soc., 2013)

(untitled) - Huang, B.; He, Y.; Levin, M. D.; Coelho, J. A. S.; Bergman, R. G.; Toste, F. D. (Adv. Synth. Catal., 2020)

(untitled) - Zhang, Q.-X.; Li, Y.; Wang, J.; Yang, C.; Liu, C.-J.; Li, X.; Cheng, J.-P. (Angew. Chem., Int. Ed., 2020)

(untitled) - James, T.; van Gemmeren, M.; List, B. (Chem. Rev., 2015)